Architecture for instantaneous frequency and amplitude detection - Lorsawatsiri, Anuree; Kiranon, Wiwat; Wongtaychatham, Chariya; Sangpisit, Wipa; Wardkein, Paramote (My University, 2011)
This paper presents a new architecture to detect the frequency and amplitude of sinusoidal signals. The proposed architecture employs merely differentiators and analog computational units to gain an accurate and instantaneous response. The detected output of the frequency measuring module is linear with frequencies and insensitive to the peak amplitude of the input signal, and vice versa. Moreover, the sensitivity (gain) of frequency detection module and that of amplitude detection module are orthogonally adjusted. The simulation results are then given to verify the theoretical analyses. The results also include various set of simulation aiming to give substantive measures of satisfactory performance of the proposed method. © 2010 Elsevier GmbH. All rights reserved.
Keywords: Amplitude detection; Architecture; Differentiating circuit; Frequency detection